Aqueous barrier coating agent, printed material, and multilayer body

JP2025026284AActive Publication Date: 2025-02-21TOYO INK MFG CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024059456
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-08
Filing Date
2024-04-02
Publication Date
2025-02-21
Estimated Expiration
2044-04-02

AI Technical Summary

Benefits of technology

【0018】 本開示の一つの側面により、コーティング剤を経時保管した後に作製される塗工物においてガスバリア性の低下を抑制することができる。本開示の他の側面により、分散安定性が良好、かつ、水性バリアコーティング剤製造から経時保存後であってもガスバリア性が良好な水性バリアコーティング剤を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026284000001
    Figure 2025026284000001
  • Figure 2025026284000002
    Figure 2025026284000002
  • Figure 2025026284000003
    Figure 2025026284000003
Patent Text Reader

Abstract

To prevent the deterioration of gas barrier properties in a coated material produced following the prolonged storage of a coating agent.SOLUTION: Disclosed is an aqueous barrier coating agent which contains a hydrophilic resin, an inorganic layered compound, and an aqueous medium, wherein: the hydrophilic resin contains at least one that is selected from the group consisting of a polyvinyl alcohol, an ethylene-vinyl alcohol copolymer having an ethylene content ratio of 25 mol% or less, and modified bodies of these; the aqueous medium contains n-propanol and water; the content of water in the total mass of the aqueous medium is 50 mass% or more; and the content of isopropanol in the total mass of the aqueous medium is 15 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to water-based barrier coatings, prints and laminates. [Background technology]

[0002] Traditionally, aluminum foil and aluminum-deposited plastic films and papers have been widely used for materials that require oxygen barrier properties, such as food packaging materials. However, in recent years, due to environmental issues and other factors, there has been a demand for thinner packaging materials, simpler lamination, and recyclability, and so technological development to eliminate aluminum is underway.

[0003] Thermoplastic resin films in which a polyvinylidene chloride (PVDC) layer is formed on a plastic film by coating exhibit high oxygen barrier properties not only under low humidity but also under high humidity, and also have high barrier properties against water vapor. However, when this PVDC-coated thermoplastic resin film is incinerated during waste disposal, there is a risk of chlorine gas and dioxin generation due to the chlorine in the PVDC, which may have a significant adverse effect on the environment and human body, and therefore there is a demand for a shift to other materials.

[0004] As a chlorine-free gas barrier coating agent, a barrier coating agent containing polyvinyl alcohol or an ethylene-vinyl alcohol copolymer is well known (Patent Document 1). It is also well known that the gas barrier property can be improved by including an inorganic layered compound in addition to polyvinyl alcohol or an ethylene-vinyl alcohol copolymer, and Patent Documents 2, 3, and 4 describe gas barrier coating agents containing a filler, polyvinyl alcohol, or an ethylene-vinyl alcohol copolymer, and state that clay mineral particles are preferable as the filler. However, as is well known in Patent Document 3 and other documents, even if polyvinyl alcohol or an ethylene-vinyl alcohol copolymer is carefully mixed with clay mineral particles, the pot life is extremely short. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2005-144761 A [Patent Document 2] JP 2015-214154 A [Patent Document 3] JP 2019-94502 A [Patent Document 4] JP 2015-208924 A [Patent Document 5] JP 2003-268183 A [Patent Document 6] JP 2003-231789 A [Patent Document 7] JP 2011-031455 A Summary of the Invention [Problem to be solved by the invention]

[0006] Generally, the above-mentioned barrier coating agents often have problems with low-temperature storage stability, and often have problems with the gas barrier properties and coating properties of the gas barrier layer. In addition, as described in the Background Art, when an inorganic layered compound is contained, there may be problems with the dispersion stability of the inorganic layered compound and deterioration of the oxygen barrier properties due to printing defects caused by gelation of the coating agent.

[0007] According to the disclosures of Patent Documents 5, 6 and 7, a combination of water and an alcohol-based organic solvent is suitable for an ethylene-vinyl alcohol copolymer having a high ethylene content in terms of immediate solubility. On the other hand, according to the disclosure of Patent Document 5, an ethylene-vinyl alcohol copolymer having a low ethylene content is provided as a solution of the ethylene-vinyl alcohol copolymer mainly made of water. In the prior art, a coating agent using an ethylene-vinyl alcohol copolymer having a low ethylene content is provided as an aqueous solution mainly made of water because of its high immediate solubility in water. On the other hand, when a coating agent using an ethylene-vinyl alcohol copolymer is stored and then applied to a substrate to obtain a coating, the gas barrier property of the coating decreases.

[0008] One object of the present disclosure is to suppress the deterioration of gas barrier properties in a coated product produced after storing the coating agent over time. Yet another object of the present disclosure is to provide an aqueous barrier coating agent having good dispersion stability of an inorganic layered compound and good gas barrier properties even after storage over time from the production of the barrier coating agent. [Means for solving the problem]

[0009] As a result of extensive research into the above-mentioned problems, the inventors have found that the above-mentioned problems can be solved by using several of the embodiments described below, and have thus completed the present invention.

[0010] [1] An aqueous barrier coating agent comprising a hydrophilic resin, an inorganic layered compound, and an aqueous medium, wherein the hydrophilic resin comprises at least one selected from the group consisting of polyvinyl alcohol, an ethylene-vinyl alcohol copolymer having an ethylene content of 25 mol% or less, and modified products thereof, and the aqueous medium comprises normal propanol and water, the water content of the aqueous medium being 50 mass% or more and the isopropanol content of the aqueous medium being 15 mass% or less.

[0011] [2] The aqueous barrier coating agent according to [1], wherein the ethylene-vinyl alcohol copolymer has an ethylene content of 20 mol % or less.

[0012] [3] The aqueous barrier coating agent according to [1] or [2], wherein the viscosity change rate represented by the following formula 1 is 30% or less. (Formula 1) Viscosity change rate = |Viscosity B - Viscosity A| / Viscosity A x 100 (In the above formula 1, viscosity A represents the viscosity at 25°C of the aqueous barrier coating agent immediately after production or stored at a temperature of 15 to 35°C after production, and viscosity B represents the viscosity of the aqueous barrier coating agent measured at 25°C after being left to stand at 5°C for 24 hours. Viscosity A and viscosity B are each the number of seconds (seconds) until flow in viscosity measurement using a Zahn cup No. 3.)

[0013] [4] The aqueous barrier coating agent according to any one of [1] to [3], wherein the hydrophilic resin accounts for 50 to 95 mass % of the total solid content of the aqueous barrier coating agent. [5] The aqueous barrier coating agent according to any one of [1] to [4], wherein the n-propanol is present in an amount of 5 mass% or more based on the total mass of the aqueous medium. [6] The aqueous barrier coating agent according to any one of [1] to [6], wherein the total content of the secondary monoalcohol and the tertiary monoalcohol is 15 mass% or less of the total mass of the aqueous medium.

[0014] [7] The aqueous barrier coating agent according to any one of [1] to [6], wherein the inorganic layered compound comprises at least one selected from the group consisting of montmorillonite, kaolinite, and natural mica. [8] The aqueous barrier coating agent according to any one of [1] to [7], wherein the inorganic layered compound comprises an inorganic layered compound having an aspect ratio of 50 to 1000. [9] The aqueous barrier coating agent according to any one of [1] to [8], wherein the inorganic layered compound contains sodium ions.

[0015]

[10] The aqueous barrier coating agent according to any one of [1] to [9], further comprising a sodium salt compound.

[11] The aqueous barrier coating agent according to any one of [1] to

[10] , wherein the inorganic layered compound in the aqueous barrier coating agent has an average particle size (D50) of 3 μm or less according to a laser diffraction / scattering method.

[12] The aqueous barrier coating agent according to any one of [1] to

[12] , wherein the inorganic layered compound accounts for more than 20 mass % and not more than 40 mass % of the total mass of solids in the aqueous barrier coating agent.

[0016]

[13] The aqueous barrier coating agent according to any one of [1] to

[13] , wherein the inorganic layered compound contains montmorillonite, and the content of the montmorillonite in the inorganic layered compound is 50 to 100 mass %.

[14] A printed matter comprising a substrate and a barrier coat layer formed from the aqueous barrier coating agent according to any one of [1] to

[13] .

[15] A laminate comprising: a substrate 1; a barrier coat layer formed by the aqueous barrier coating agent according to any one of [1] to

[13] ; and a substrate 2, wherein the barrier coat layer is interposed between the substrate 1 and the substrate 2.

[0017]

[16] A method for producing an aqueous barrier coating agent, comprising: mixing a hydrophilic resin containing at least one selected from the group consisting of polyvinyl alcohol, an ethylene-vinyl alcohol copolymer having an ethylene content of 25 mol% or less, and modified products thereof, and controlling the temperature at 80°C or more for one hour or more to provide a pre-hydrophilic resin composition; mixing the pre-hydrophilic resin composition and normal propanol to provide a hydrophilic resin composition; and mixing the hydrophilic resin composition and an inorganic layered compound to provide an aqueous barrier coating agent, wherein the aqueous barrier coating agent is an aqueous medium containing normal propanol and water, the content of water in the total mass of the aqueous medium is 50 mass% or more, and the content of isopropanol in the total mass of the aqueous medium is 15 mass% or less. Effect of the Invention

[0018] According to one aspect of the present disclosure, it is possible to suppress the deterioration of the gas barrier property in a coated product produced after storing the coating agent over time. According to another aspect of the present disclosure, it is possible to provide an aqueous barrier coating agent having good dispersion stability and good gas barrier property even after storing the aqueous barrier coating agent over time from its production. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Several embodiments of the present invention will be described in detail below. However, the described embodiments or explanations of the requirements are examples of the embodiments of the present invention, and the present invention is not limited to these contents as long as they do not exceed the gist of the present invention.

[0020] A representative embodiment of the present invention is an aqueous barrier coating agent (hereinafter, also simply referred to as a "coating agent"). The aqueous barrier coating agent can be printed on a substrate to form a barrier coat layer, thereby providing a printed matter. The printed matter can be laminated with another substrate to provide a laminate.

[0021] The aqueous barrier coating agent according to the present disclosure comprises a hydrophilic resin, an inorganic layered compound, and an aqueous medium, wherein the hydrophilic resin comprises at least one selected from the group consisting of polyvinyl alcohol, an ethylene-vinyl alcohol copolymer having an ethylene content of 25 mol% or less, and modified products thereof, and the aqueous medium comprises normal propanol and water, the water content of the aqueous medium being 50 mass% or more and the isopropanol content of the aqueous medium being 15 mass% or less.

[0022] According to this aqueous barrier coating, good gas barrier properties can be obtained in a printed matter or laminate formed using the coating agent, even immediately after production of the coating agent and after storage over time. For example, there is a phenomenon in which the gas barrier properties are reduced in a printed matter or laminate formed using the coating agent after storage over time. As a result of intensive research into the cause of this, attention was focused on the fact that the coating agent is exposed to a low-temperature environment during storage over time. When a coating agent containing polyvinyl alcohol, an ethylene-vinyl alcohol copolymer, a modified product thereof, or a combination thereof is exposed to a low-temperature environment during storage, gelation of these hydrophilic resins is likely to occur in the coating agent. Once gelation occurs in the coating agent, a reduction in gas barrier properties can be caused in a printed matter or laminate produced using this coating agent. In the present disclosure, it has been found that a coating agent containing normal propanol together with a hydrophilic resin and an inorganic layered compound, within a range in which the water content in the total mass of the aqueous medium is 50 mass% or more and the isopropanol content in the total mass of the aqueous medium is 15 mass% or less, can suppress the deterioration of the gas barrier property of a printed matter or laminate formed using the coating agent even after storage over time. This effect can be confirmed significantly, especially after storage over time in a low-temperature environment. Furthermore, this effect is particularly effective for oxygen barrier property among gas barrier properties, and is useful for packaging materials for food and medicine.

[0023] In this way, the deterioration of the gas barrier property of the printed matter or laminate can be improved by controlling the shelf life of the coating agent. Therefore, the technical idea of ​​the present invention is to provide a means for ensuring the shelf life of the coating agent. It is known that the shelf life of the coating agent is greatly affected by the state of the aqueous solution immediately after production. It is considered that the gelation of the coating agent shown in the conventional technology is caused by the micro state of the aqueous solution. One method for evaluating this state is the pot life. For example, the coating agent shown in the conventional technology has a pot life of less than 24 hours, and the shelf life is not sufficient. In addition, the evaluation method of the pot life of the conventional technology cannot fully evaluate the shelf life of the coating agent to the extent that it can affect the deterioration of the gas barrier property of the printed matter or laminate.

[0024] In the present disclosure, it is preferable that the shelf life of the coating agent is improved when the coating agent is stored at room temperature after production, when the coating agent is stored at a low temperature, or when the coating agent is stored at a combination of these. For example, it is preferable that the shelf life of the coating agent is improved even in a low-temperature environment of about 5°C.

[0025] <Viscosity change rate> For the long-term storage stability of a coating agent, it is important to precisely control the viscosity change rate between one that has not been subjected to low-temperature heat history and one that has been subjected to low-temperature heat history. Some embodiments provide a formulation in which such a viscosity change rate is precisely controlled within a formulation range that has gas barrier properties.

[0026] In some embodiments, the aqueous barrier coating agent may have a viscosity change rate, represented by the following formula 1, of 30% or less. (Formula 1) Viscosity change rate = |Viscosity B - Viscosity A| / Viscosity A x 100 (In the above formula 1, viscosity A represents the viscosity at 25°C of the aqueous barrier coating agent immediately after production or stored at a temperature of 15 to 35°C after production, and viscosity B represents the viscosity of the aqueous barrier coating agent measured at 25°C after being left to stand at 5°C for 24 hours. Viscosity A and viscosity B are each the number of seconds it takes for the aqueous barrier coating agent to flow out in viscosity measurement using a Zahn cup No. 3.)

[0027] Here, |viscosity B-viscosity A| represents the absolute value of the difference between viscosity A and viscosity B. Zahn cup No. 3 manufactured by Rigo Co., Ltd. can be used as Zahn cup No. 3. Rigo Co., Ltd. Zahn cup No. 3 is made of stainless steel, has a cup capacity of 43 ml, and an orifice diameter of 3 mm. The outflow time is the number of seconds from the moment the cup submerged in the sample is pulled up with a quick and constant movement and the moment the flow of the sample outflowing from the orifice (steady flow) stops when the bottom of the cup leaves the liquid surface. Viscosity B may be, for example, the viscosity of the aqueous barrier coating agent measured at a temperature of 25°C after leaving it at rest for 24 hours at 5°C in a sealed container so that the solvent does not evaporate. For details of the measurement method, see the Examples.

[0028] Aqueous barrier coating agents of the prior art tend to thicken upon memorizing a thermal history at low temperatures (for example, 5°C or less). In some embodiments, the barrier coating agent may have a viscosity change rate of 30% or less between one that has not been subjected to a thermal history at low temperatures and one that has been subjected to a thermal history at low temperatures. The viscosity change rate is preferably 25% or less, and more preferably 20% or less. When the viscosity change rate is within these ranges, the gas barrier properties of the printed matter and laminate can be maintained better. In addition, since the appropriate viscosity is maintained even after storage over time, the amount of coating during printing is stable, and the gas barrier properties of the printed matter and laminate can be maintained better.

[0029] Means for controlling the viscosity change rate of the aqueous barrier coating agent to the above range are shown below. For example, it is preferable to increase the temperature (dissolution temperature) when dissolving the hydrophilic resin in the aqueous medium, or to lengthen the dissolution time, or a combination of these. The dissolution temperature is preferably 80°C or higher, more preferably 85°C or higher, even more preferably 90°C or higher, and even more preferably 95°C or higher. The dissolution time is preferably 1 hour or longer. For example, the dissolution temperature may be 80 to 100°C, and the dissolution time may be 1 to 3 hours. In addition, when the hydrophilic resin is dissolved in water and heated, it is more preferable to add normal propanol after returning to room temperature. This is because under these conditions, the dispersion stability of the hydrophilic resin itself in the coating agent is further increased, and viscosity change is less likely to occur even after low-temperature thermal history.

[0030] <Hydrophilic resin> In some embodiments, the hydrophilic resin comprises at least one selected from the group consisting of polyvinyl alcohol, an ethylene-vinyl alcohol copolymer having an ethylene content of 25 mol% or less, and modified products thereof. The hydrophilic resin preferably comprises an ethylene-vinyl alcohol copolymer having an ethylene content of 25 mol% or less, a modified product thereof, or a combination thereof (hereinafter, these are collectively referred to as ethylene-vinyl alcohol copolymers).

[0031] The ethylene-vinyl alcohol copolymer is a copolymer having an ethylene unit and a vinyl alcohol unit. The ethylene-vinyl alcohol copolymer may further contain a vinyl ester unit. In the ethylene-vinyl alcohol copolymer, the vinyl ester unit is preferably 10 mol % or less, or 5 mol % or less. The ethylene-vinyl alcohol copolymer may be a saponified ethylene-vinyl ester copolymer. The ethylene-vinyl ester copolymer can be synthesized using ethylene and a vinyl ester monomer. Examples of the vinyl ester monomer include formic acid, vinyl acetate, vinyl propionate, etc., and vinyl acetate is industrially preferred.

[0032] The content ratio of ethylene-derived structures in the case of containing ethylene-vinyl alcohol copolymers (hereinafter also referred to as ethylene content ratio, equal to the raw material charge mol % ratio) is preferably 25 mol % or less, more preferably 22 mol % or less, 20 mol % or less, or 18 mol % or less. In these ranges, the gas barrier property can be maintained better. Ethylene-vinyl alcohol copolymers with low ethylene content ratios tend to have low gas barrier property by themselves, but by using water as the main component in an aqueous medium in combination with water and normal propanol, the gas barrier property of the resulting printed matter or laminate can be improved. For example, the ethylene content ratio is preferably 0.1 to 15 mol %, more preferably 5 to 13 mol %, and more preferably 7 to 11 mol %. By being in these ranges, the gas barrier property becomes better. From the viewpoint of improving the low-temperature storage stability of the coating agent while providing the gas barrier properties of the printed matter or laminate, the ethylene content may be 15 mol% or less, 13 mol% or less, 11 mol% or less, 10 mol% or less, 8 mol% or less, 6 mol% or less, 4 mol% or less, or 2 mol% or less. In this case, the lower limit may be 0.1 mol%, 0.5 mol%, or 1 mol%, respectively.

[0033] The ethylene content can be determined by subjecting the raw material of ethylene-vinyl alcohol copolymers or the esterified product thereof, ethylene-vinyl ester copolymer, to nuclear magnetic resonance (NMR) measurement.

[0034] By using water as the main component in an aqueous medium in combination with water and normal propanol, the gas barrier properties of the resulting printed matter or laminate can be improved, and therefore the hydrophilic resin may contain polyvinyl alcohol, a modified product thereof, or a combination of these (hereinafter, these are collectively referred to as polyvinyl alcohols).

[0035] The polymerization degree of each of the polyvinyl alcohols and ethylene-vinyl alcohol copolymers is preferably from 100 to 3000, and more preferably from 500 to 2400. When it is within these ranges, the gas barrier property becomes better.

[0036] Polyvinyl alcohols and ethylene-vinyl alcohol copolymers are produced by saponifying the acetyl group derived from vinyl acetate to a hydroxyl group, but it is also preferable that the hydroxyl group is further modified. Specifically, it is preferable to modify the hydroxyl group to have a modified functional group (modified group). The modification may be, but is not limited to, known modification means such as carbonyl modification and silicon modification. In addition, polyvinyl alcohols and ethylene-vinyl alcohol copolymers crosslinked with a crosslinking agent may be used. Examples of the crosslinking agent used in this case include known crosslinking agents such as isocyanate, epoxy, melamine, oxazoline, and silane coupling agents, with oxazoline and silane coupling agents being preferred.

[0037] The saponification degree of polyvinyl alcohols is represented by the following formula 2, and is preferably 80 mol% or more, more preferably 90 mol% or more, and preferably 95 mol% or more. When it is within these ranges, the gas barrier property becomes better. The polyvinyl alcohols may be fully saponified polyvinyl alcohol. (Formula 2) Saponification degree = (number of hydroxyl groups) / {(number of hydroxyl groups) + (number of acetyl groups)} × 100 [mol %]

[0038] In the ethylene-vinyl alcohol copolymers, the degree of saponification of the vinyl ester-derived units is preferably in the same range as that of the above-mentioned polyvinyl alcohols.

[0039] The hydrophilic resin is preferably 1 to 20% by mass, more preferably 2 to 15% by mass, particularly preferably 3 to 10% by mass, and even more preferably 5 to 10% by mass or 6 to 10% by mass, based on the total mass of the coating agent. When polyvinyl alcohols and ethylene-vinyl alcohol copolymers are used alone, the content of the polyvinyl alcohols is preferably 5 to 20% by mass or 6 to 10% by mass. When ethylene-vinyl alcohol copolymers are used alone, the content of the ethylene-vinyl alcohol copolymers is more preferably 5 to 20% by mass or 6 to 10% by mass. According to this embodiment, a larger amount of hydrophilic resin can be contained while maintaining good dispersion stability.

[0040] The hydrophilic resin is preferably 50 to 95 mass % of the total mass of the solid content of the coating agent, more preferably 60 to 90 mass %, and particularly preferably 70 to 80 mass %. In the present disclosure, the solid content refers to the components remaining after the coating agent is dried to a state where there is no mass change when the coating agent is heat-treated at 100°C.

[0041] Examples of polyvinyl alcohols and ethylene-vinyl alcohol copolymers that can be used include Kuraray Poval R series (polyvinyl alcohol resin, manufactured by Kuraray Co., Ltd.), Kuraray Exeval AQ-4104, RS-2117 (specially modified polyvinyl alcohol, manufactured by Kuraray Co., Ltd.), Kuraray Eval L104B, F104B (ethylene-vinyl alcohol copolymer resin, manufactured by Kuraray Co., Ltd.), etc.

[0042] In some embodiments, the coating agent may contain a resin other than polyvinyl alcohols and ethylene-vinyl alcohol copolymers as a hydrophilic resin, and specific examples include polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, acrylic resin, etc. These resins may be used alone or in a mixture of two or more. The total mass of polyvinyl alcohols and ethylene-vinyl alcohol copolymers relative to the total mass of resins contained in the coating agent may be 20% by mass or more, 50% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more, with the upper limit being in the range of 100% by mass, 99% by mass, or 98% by mass.

[0043] <Inorganic layered compounds> In some embodiments, the coating agent contains an inorganic layered compound. The inclusion of the inorganic layered compound improves the gas barrier property. The inorganic layered compound referred to here is a compound in which unit crystal layers are stacked to form a layered structure, and is preferably one that swells and cleaves in an aqueous medium.

[0044] It is preferable to select an inorganic layered compound that is compatible with an aqueous medium. In addition, when the inorganic layered compound and its interlayer ions contain sodium ions, the swelling property is increased and the interlayer distance is increased, so that aggregation and precipitation are unlikely to occur, and dispersion stability and gas barrier properties are better, which is preferable. In addition, from the viewpoint of gas barrier properties, it is preferable that the inorganic layered compound contains an inorganic layered compound having an aspect ratio of 10 to 2000 or 50 to 1000.

[0045] Preferred examples of inorganic layered compounds include montmorillonite, beidellite, saponite, hectorite, sauconite, vermiculite, mica, paragonite, lepidolite, margarite, clintonite, anandite, chlorite, donbassite, sudoite, cookeite, clinochlore, chamosite, nimite, tetrasilylic mica, talc, pyrophyllite, nacrite, kaolinite, halloysite, chrysotile, sodium teniolite, xanthophyllite, antigorite, dickite, hydrotalcite, etc., and more preferably selected from montmorillonite, kaolinite, and natural mica. Preferably, it contains at least one selected from the group consisting of montmorillonite, kaolinite, and natural mica, and particularly preferably montmorillonite.

[0046] For example, the content of the inorganic layered compound in the solid content of the aqueous barrier coating agent is preferably 5 to 50 mass%, more preferably 10 to 40 mass%, and even more preferably 20 to 30 mass% based on 100 mass% of the solid content. This is because it prevents precipitation of the inorganic layered compound and gelation of the coating agent, and makes viscosity changes less likely to occur. From this perspective, the content of the inorganic layered compound is preferably more than 20 mass% and not more than 40 mass% based on the total mass of the solid content of the aqueous barrier coating agent.

[0047] <Montmorillonite> Montmorillonite used in some embodiments is represented by the following formula 3. Bentonite containing montmorillonite as a main component and further containing minerals such as quartz and feldspar can also be used. (Formula 3) MaSi4(Al 2-a Mg a )O 10 (OH)2 nH2O (In formulas 3 to 6, M represents an interlayer cation, a is 0.25 to 0.60, and nH2O represents the number of water molecules.) Montmorillonite also includes isomorphous ion-substituted products of magnesian montmorillonite, iron montmorillonite, and iron magnesian montmorillonite represented by the following formulas 4 to 6, and these may also be used. (Formula 4) MaSi4(Al 1.67-a Mg 0.5+a )O 10 (OH)2 nH2O (Formula 5) MaSi4(Fe 2-a 3+ Mg a )O 10 (OH)2 nH2O (Formula 6) MaSi4(Fe 1.67-a 3+ Mg 0.5+a )O 10 (OH)2 nH2O

[0048] The interlayer cations include inorganic cations such as sodium ions, calcium ions, magnesium ions, and potassium ions, and organic cations such as quaternary ammonium ions. From the viewpoint of affinity to water, inorganic cations are preferred, and sodium ions and / or calcium ions are more preferred. It is even more preferred to contain sodium ions. In addition, it is preferred to use montmorillonite purified by water treatment.

[0049] The volume-average particle thickness of montmorillonite is preferably 0.05 to 30 nm, more preferably 0.1 to 10 nm, and even more preferably 0.5 to 3 nm. The volume-average particle major axis of montmorillonite is preferably 0.01 to 5 μm, more preferably 0.05 to 3 μm, and even more preferably 0.1 to 1 μm. In addition, the volume-average particle aspect ratio of montmorillonite is preferably 10 to 2000, more preferably 50 to 1000, even more preferably 100 to 1000, and particularly preferably 300 to 700. By being within these ranges, the gas barrier property becomes better. In the present disclosure, the particle thickness, particle major axis, and particle aspect ratio of montmorillonite can be measured by an atomic force microscope (AFM).

[0050] As the montmorillonite, commercially available products such as Kunipia-F and Kunipia-G (manufactured by Kunimine Kogyo Co., Ltd.) can be used.

[0051] When montmorillonite is used, from the viewpoint of gas barrier properties, it is preferable that the montmorillonite accounts for 10 mass% or more, 30 mass% or more, 50 mass% or more, 80 mass% or more, 90 mass% or more, or 95 mass% or more of the inorganic layered compound, with the upper limit being 100 mass%, 99 mass%, or 98 mass%, respectively. Montmorillonite may be used alone as the inorganic layered compound.

[0052] <Hectorite> The hectorite used in some embodiments is represented by Formula 7 below and may be natural or synthetic. (Formula 7)Na 0.3 Si4(Mg 2.7 Li 0.3 )O 10 (OH)2 nH2O

[0053] The volume average particle thickness of the hectorite is preferably 0.05 to 30 nm, more preferably 0.1 to 10 nm, and even more preferably 0.5 to 3 nm. The particle aspect ratio is preferably 10 to 1000, more preferably 100 to 500, and even more preferably 20 to 200. By being within these ranges, the gas barrier property becomes better. In some embodiments, the particle thickness, particle length, and particle aspect ratio of hectorite can be measured by scanning electron microscopy (SEM).

[0054] As the hectorite, commercially available products such as Laponite JS and Laponite S482 (manufactured by BYK Japan Co., Ltd.) can be used.

[0055] <Kaolinite> The kaolinite used in some embodiments is mainly composed of kaolinite (Al2O3·2SiO2·H2O) or halloysite Al2O3·2SiO2·2H2O, and may be a natural product or a synthetic product. In addition, depending on the manufacturing method, there are dry kaolinite, wet kaolinite, calcined kaolin, etc., but are not limited to these.

[0056] From the viewpoint of gas barrier properties, the volume-average particle size of kaolinite is preferably 1 to 100 μm, more preferably 3 to 50 μm, and even more preferably 5 to 20. The volume-average aspect ratio of kaolinite is preferably 10 to 1,000, more preferably 30 to 500, and even more preferably 50 to 200. In some embodiments, the particle size of kaolinite can be measured by laser diffraction / scattering, and the aspect ratio can be measured by a scanning electron microscope (SEM).

[0057] As the kaolinite, commercially available products such as Varisurf HX (manufactured by Imerys), NN kaolin clay, and ST kaolin clay (manufactured by Takehara Chemical Industry Co., Ltd.) can be used.

[0058] <Mica> The mica used in some embodiments may be either natural or synthetic mica. Natural mica is a scaly base material made by crushing mica ore, and the particle size and aspect ratio can be controlled by mechanical crushing or cleavage by calcination. Synthetic mica includes those synthesized by heating industrial raw materials such as SiO2, MgO, Al2O3, K2SiF6, and Na2SiF6, melting them at a high temperature of about 1500°C, and then cooling and crystallizing them.

[0059] From the viewpoints of printability and gas barrier properties, the volume-average particle size of the mica is preferably 30 μm or less, more preferably 1 to 25 μm, and even more preferably 5 to 15 μm, and the volume-average aspect ratio of the mica is preferably 30 to 200, more preferably 70 to 170, and even more preferably 100 to 150. In the present disclosure, the particle size of mica can be measured by a laser diffraction / scattering method, and the aspect ratio can be measured by a scanning electron microscope (SEM).

[0060] As the mica, commercially available products such as Mica Powder TM series, Mica Powder NCF series (manufactured by Yamaguchi Mica Co., Ltd.), L60M, L100M (manufactured by Seishin Enterprise Co., Ltd.) and the like can be used.

[0061] <Sodium salt compounds> In some embodiments, the aqueous barrier coating agent preferably contains a sodium salt compound, more preferably a sodium salt compound containing an oxo acid. By containing the sodium salt compound, the dispersion stability of the inorganic layered compound is improved. This is believed to be because a part or all of the sodium ions derived from the sodium salt compound compensate for the interlayer ions of the inorganic layered compound. Specific examples of the sodium salt compound containing an oxoacid include sodium carbonate, sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate.

[0062] When a sodium salt compound is used, the amount of the sodium salt compound containing an oxo acid added in the solid content of the aqueous barrier coating agent is preferably 0.1 to 10 mass %, more preferably 0.2 to 5 mass %, and even more preferably 0.3 to 3 mass %, relative to 100 mass % of the inorganic layered compound.

[0063] <Aqueous medium> In some embodiments, the coating agent includes an aqueous medium. The aqueous medium includes normal propanol and water, and the content of water in the total mass of the aqueous medium is preferably 50% by mass or more, and the content of isopropanol in the total mass of the aqueous medium is preferably 15% by mass or less. The main component of the aqueous medium (50% by mass or more of the aqueous medium) is preferably water, and normal propanol can be used in addition to water. In addition to normal propanol, an additional hydrophilic organic solvent may be used, specifically, an alcohol-based organic solvent, a glycol-based organic solvent, an ether-based organic solvent, or the like can be contained. An alcohol-based organic solvent is preferable. An aqueous medium containing water and normal propanol can improve the gas barrier properties of the resulting printed matter or laminate. In addition, when the aqueous medium contains normal propanol alone or in combination with an additional hydrophilic organic solvent, the drying property of the printed matter and the defoaming effect of the coating agent can be further improved in printing. By controlling the isopropanol content in the total mass of the aqueous medium to 15 mass % or less, the dispersion stability of the coating agent can be obtained even after storage over time in a low-temperature environment, and the gas barrier properties of the resulting printed matter or laminate can be improved.

[0064] The content of the aqueous medium in the aqueous barrier coating agent is preferably 60 to 99 mass %, more preferably 70 to 98 mass %, and particularly preferably 80 to 97 mass %, based on the total mass of the coating agent. The hydrophilic organic solvent is contained in an amount of preferably 5 to 45 mass %, more preferably 11 to 40 mass %, and further preferably 20 to 35 mass %, based on the total mass of the aqueous medium. The hydrophilic organic solvent is preferably contained in an amount of 4 to 42 mass % of the total mass of the coating agent, more preferably 10 to 37 mass %, and even more preferably 18 to 33 mass %. The water content of the aqueous medium is preferably 50% by mass or more, for example, 50 to 99% by mass, 55 to 90% by mass, 60 to 85% by mass, or 65 to 80% by mass. The water content of the coating agent is preferably 45% by mass or more, for example, 45 to 98% by mass, 50 to 90% by mass, 55 to 85% by mass, or 60 to 80% by mass.

[0065] (Normal Propanol) The aqueous medium preferably contains normal propanol, and the mass ratio of normal propanol in the total mass of the coating agent is preferably 1 mass% or more, more preferably 5 mass% or more, even more preferably 11 mass% or more, and particularly preferably 20 mass% or more. In these ranges, the gas barrier property of the resulting printed matter or laminate can be further improved. In addition, by being in these ranges, the dispersion stability of the coating agent during storage over time can be increased, and viscosity changes due to gelation can be prevented. For example, the mass ratio of normal propanol in the total mass of the coating agent may be 1 to 50 mass%, 5 to 45 mass%, 11 to 40 mass%, or 20 to 30 mass%.

[0066] The mass ratio of normal propanol in the total mass of the aqueous medium is preferably 1% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more or 15% by mass or more, and particularly preferably 20% by mass or more. In these ranges, the gas barrier property of the resulting printed matter or laminate can be further improved. In addition, by being in these ranges, the dispersion stability of the coating agent during storage over time can be increased, and viscosity changes due to gelation can be prevented. For example, the mass ratio of normal propanol in the total mass of the aqueous medium may be 1 to 50% by mass, 5 to 45% by mass, 10 to 40% by mass, or 15 to 30% by mass.

[0067] When the aqueous medium contains normal propanol and water, and the content of water in the total mass of the aqueous medium is 50% by mass or more, the content of isopropanol in the total mass of the aqueous medium is preferably 15% by mass or less, more preferably 12% by mass or less, even more preferably 10% by mass or less, and particularly preferably 8% by mass or less. In these ranges, the dispersion stability of the coating agent can be obtained even after storage over time in a low-temperature environment, and the gas barrier property of the resulting printed matter or laminate can be improved. From the viewpoint of gas barrier property, the content of isopropanol in the total mass of the aqueous medium may be 0% by mass, 0 to 5% by mass, 0 to 2% by mass, or 0 to 1% by mass.

[0068] The mass ratio of isopropanol in the total mass of the coating agent may be 0 mass%, and is preferably 15 mass% or less, 12 mass% or less, 10 mass% or less, or 8 mass% or less. From the viewpoint of further improving the gas barrier property, the mass ratio of isopropanol in the total mass of the coating agent may be 0 mass%, or may be 0 to 5 mass%, 0 to 2 mass%, or 0 to 1 mass%.

[0069] (Secondary and / or tertiary monoalcohols) In some embodiments, the additional hydrophilic organic solvent may include at least one selected from the group consisting of secondary monoalcohols and tertiary monoalcohols. The total content of the secondary monoalcohols and tertiary monoalcohols is preferably 0% by mass or less or 15% by mass or less of the total mass of the aqueous medium. For example, in order to make the viscosity change rate of the coating agent represented by formula 1 30% or less, the aqueous medium preferably contains 15% by mass or less of secondary monoalcohols and / or tertiary monoalcohols. The total content of the secondary monoalcohols and tertiary monoalcohols is preferably 0 or 15% by mass or less of the total mass of the aqueous medium, preferably less than 0 or 10% by mass, preferably 0 or 8% by mass or less, and more preferably 0 or 5% by mass or less. In these ranges, the gas barrier properties of the resulting printed matter or laminate can be further improved. In addition, by being in these ranges, the dispersion stability of the coating agent during storage over time is increased, and viscosity change due to gelation can be prevented. The total content of the secondary monoalcohols and tertiary monoalcohols includes the content of isopropanol.

[0070] The secondary monoalcohol and / or tertiary monoalcohol may have 3 to 6 carbon atoms, more preferably 3 or 4, and examples thereof include isopropanol, tert-butanol, sec-butanol, etc. These may be used alone or in combination of two or more kinds.

[0071] Other examples of the alcohol-based organic solvent include alcohol-based organic solvents having 1 to 20, 1 to 10, or 1 to 8 carbon atoms. Specific examples of the alcohol-based organic solvent include methanol, ethanol, normal butanol, hexanol, octanol, and decanol. These may be used alone or in combination of two or more.

[0072] Examples of the glycol-based organic solvent include acetylene diol, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, etc. These may be used alone or in combination of two or more. Propylene glycol is preferred.

[0073] Glycol ether-based organic solvents may also be used. For example, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monooctyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monopropyl ether, triethylene glycol monobutyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, tripropylene glycol monopropyl ether, tripropylene glycol monobutyl ether, dibutyl glycol, etc. may be mentioned. These may be used alone or in combination of two or more. Propylene glycol monoethyl ether is preferred.

[0074] The aqueous medium may contain 1 to 50 mass%, 5 to 50 mass%, or 10 to 50 mass% of normal propanol relative to 100 mass% of water. From the viewpoint of gas barrier properties, the aqueous medium may contain 12 to 50 mass%, 15 to 50 mass%, 20 to 50 mass%, or 30 to 50 mass% of normal propanol relative to 100 mass% of water. Within these ranges, the gas barrier properties can be further improved.

[0075] When the aqueous medium contains isopropanol, the content of normal propanol is preferably greater than that of isopropanol. For example, the aqueous medium preferably contains 90% by mass or less, 80% by mass or less, or 75% by mass or less of isopropanol relative to 100% by mass of normal propanol. Within these ranges, the gas barrier properties can be further improved.

[0076] <Method of manufacturing the aqueous barrier coating agent> The method for producing the aqueous barrier coating agent is not particularly limited, but several embodiments for producing the aqueous barrier coating agent are described below. For example, the aqueous barrier coating agent can be obtained by mixing a hydrophilic resin, an inorganic layered compound, and an aqueous medium all at once or in portions, and optionally dispersing the mixture. Preferably, the aqueous barrier coating agent can be obtained by mixing a hydrophilic resin and an aqueous medium to obtain a hydrophilic resin composition, and then mixing and dispersing the hydrophilic resin composition and the inorganic layered compound.

[0077] In some embodiments, there is provided a method for producing an aqueous barrier coating agent, comprising: mixing a hydrophilic resin containing at least one selected from the group consisting of polyvinyl alcohol, an ethylene-vinyl alcohol copolymer having an ethylene content of 25 mol% or less, and modified products thereof, and controlling the temperature at 80°C or more for one hour or more to provide a pre-hydrophilic resin composition; mixing the pre-hydrophilic resin composition and normal propanol to provide a hydrophilic resin composition; and mixing the hydrophilic resin composition and an inorganic layered compound to provide an aqueous barrier coating agent, wherein the aqueous barrier coating agent is an aqueous medium containing normal propanol and water, the content of water in the total mass of the aqueous medium is 50 mass% or more, and the content of isopropanol in the total mass of the aqueous medium is 15 mass% or less.

[0078] In this manufacturing method, it is more preferable that the temperature is controlled at 85°C or higher for 1 hour or more. In this manufacturing method, the pre-hydrophilic resin composition is preferably an aqueous solution of the hydrophilic resin composition, although a part of the hydrophilic resin may remain undissolved. In this manufacturing method, the hydrophilic resin composition is preferably a solution of the hydrophilic resin composition in water and propanol, although a part of the hydrophilic resin may remain undissolved. According to this manufacturing method, the pot life of the obtained barrier coating agent when stored at room temperature can be made to exceed 24 hours. In this manufacturing method, it is preferable that the pot life of the obtained barrier coating agent when stored at room temperature is 24 hours or less is excluded.

[0079] As a more specific example of the method, the aqueous barrier coating agent can be obtained through the following two steps. In step 1, a hydrophilic resin and an aqueous medium are charged in a stirrer equipped with stirring blades, rotors, etc., and stirred and mixed. In step 2, an inorganic layered compound is added and dispersed. The stirring speed in both steps 1 and 2 is not particularly limited, and can be performed at 50 to 2000 rpm. In step 1, stirring and mixing are preferably performed at a high temperature, and the temperature is preferably 80° C. or higher, more preferably 85° C. or higher, even more preferably 90° C. or higher, and even more preferably 95° C. or higher. For example, the dissolution temperature may be 80 to 100° C., and the dissolution time may be 1 to 3 hours. By performing the dissolution at a high temperature, gelation is unlikely to occur even during long-term storage, and the dispersion stability during storage over time is improved. In step 2, a disperser is used, but it is preferable to use not only a stirrer (disperser) but also a bead mill for dispersion, which improves the dispersion stability of the inorganic layered compound. In this manufacturing method, in the aqueous barrier coating agent obtained, the aqueous medium preferably contains normal propanol and water, the water content of the aqueous medium is 50 mass% or more, and the isopropanol content of the aqueous medium is 15 mass% or less.

[0080] In step 1, a more preferred method is to obtain a pre-hydrophilic resin composition by stirring and mixing the hydrophilic resin and water, and then add normal propanol to the pre-hydrophilic resin composition to obtain the hydrophilic resin composition. This method can further improve the gas barrier properties of a printed matter or laminate formed using the coating agent. Furthermore, this method can further suppress the occurrence of gelation of the hydrophilic resin in the coating agent even after storage over time at low temperatures.

[0081] <Average particle diameter (D50)> In some embodiments, the average particle size (D50) of the inorganic layered compound in the aqueous barrier coating agent measured by a particle size distribution analyzer is preferably 10 μm or less, more preferably 5 μm or less, and particularly preferably 3 μm or less. By being 10 μm or less, the dispersion stability of the inorganic layered compound becomes better. In the present disclosure, the average particle size (D50) measured by a particle size distribution analyzer is the particle size at which the volume-based integrated value becomes 50% in the particle size distribution measured by the laser diffraction / scattering method.

[0082] <Printed material> According to some embodiments, a printed matter is provided that includes a substrate and a barrier coat layer formed by an aqueous barrier coating agent. The aqueous barrier coating agent may be one described above. In the present disclosure, the substrate used in the printed matter is also referred to as substrate 1. In some embodiments, a printed matter having a barrier coat layer can be obtained by printing the aqueous barrier coating agent onto substrate 1. Printing can be performed by any printing method, and is not particularly limited, but gravure printing is preferably used.

[0083] <Base material, base material 1> The substrate 1 that can be used in some embodiments is not particularly limited, and examples thereof include paper substrates such as medium-quality paper, fine paper, impregnated paper, cardboard, and craft paper, and plastic substrates such as polyethylenes such as biaxially oriented polypropylene (OPP), non-oriented polypropylene (CPP), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), and uniaxially oriented polyethylene (MDOPE), acid-modified polyethylene, acid-modified polypropylene, copolymerized polypropylene, polyethylene terephthalate, polycarbonate, polylactic acid, polystyrene, AS resin, ABS resin, nylon, polyamide, polyvinyl chloride, polyvinylidene chloride, and cellophane, and substrates made of the above composite materials can also be used. In addition, the substrates may be subjected to deposition of inorganic compounds such as silica, alumina, and aluminum, or coating treatment with polyethylene or polyvinyl alcohol, or may be subjected to corona treatment. The thickness of the substrate 1 is not particularly limited, but in consideration of the processability of the printed matter or laminate, it is preferably from 5 μm to 150 μm, more preferably from 10 μm to 70 μm.

[0084] The substrate 1 may be a single layer, may simply be a laminate of plastic substrates, or may be a laminate of the same or different substrates. The "different substrates" may be of any type, including plastic substrates and paper substrates having different properties. In the case of a laminated substrate, it may be in a form including an adhesive layer. The method of lamination is not particularly limited, and may be a conventionally known method such as co-extrusion, heat fusion, or pressure bonding via an adhesive layer.

[0085] <Manufacturing method of printed matter> In some embodiments, the aqueous barrier coating agent is diluted with a diluting solvent to a viscosity and concentration suitable for gravure printing, for example, and then supplied to a printing unit and applied to the substrate 1. Thereafter, the coating is fixed by drying in an oven or the like, thereby obtaining a printed matter provided with a barrier coat layer.

[0086] The coating weight of the barrier coat layer after drying is 0.1 to 5 g / m 2 It is preferable that the thickness is 0.3 to 3 g / m 2 More preferably, the thickness is 0.5 to 1.5 g / m 2 When it is within these ranges, the gas barrier property and the adhesion to the substrate are further improved.

[0087] <Laminate> According to some embodiments, a laminate is provided that includes a substrate 1, a barrier coat layer formed by an aqueous barrier coating agent, and a substrate 2, with the barrier coat layer being interposed between the substrate 1 and the substrate 2. The aqueous barrier coating agent may be one described above. The substrate 1 may be one described above as the substrate for the printed matter. The laminate includes a substrate 1, a barrier coat layer formed by an aqueous barrier coating agent, and a substrate 2 in this order, and the layers may be directly laminated to each other, or an intermediate layer may be interposed between the layers.

[0088] A laminate can be obtained by further laminating a substrate 2 on the barrier coat layer of a printed matter having a barrier coat layer on a substrate 1. Specific examples of the structure of the laminate include, but are not limited to, the following structures. In the structure descriptions (1) to (5) below, " / " indicates the boundary between layers.

[0089] Since the anchor coat layer can fill in minute irregularities on the substrate surface, forming a barrier coat layer on the anchor coat layer makes the barrier coat layer uniform and can suppress the occurrence of pinholes. Depending on the substrate used, an isocyanate-based curing agent can be added to the anchor coat layer to improve adhesion to the substrate. The adhesive layer is not limited to those composed of adhesives used in the conventionally known methods of dry lamination and non-solvent lamination, but also includes cases where the adhesive layer is composed of a polyolefin resin or other thermoplastic resin layer in extrusion lamination. The print layer is a layer provided separately from the barrier coat layer in order to provide various information and designs to the laminate. The names of the layers are based on their functions in terms of the form of use, and the substrate 1, substrate 2, thermoplastic resin layer, and intermediate substrate may not be distinguishable from the viewpoint of the materials. Each layer may be a single layer or multiple layers. (1) Substrate 1 / Barrier Coat Layer (2) Substrate 1 / barrier coat layer / adhesive layer / substrate 2 (3) Substrate 1 / anchor coat layer / barrier coat layer / adhesive layer / intermediate substrate / adhesive layer / substrate 2 (4) Substrate 1 / anchor coat layer / barrier coat layer / adhesive layer / first intermediate substrate / adhesive layer / second intermediate substrate / adhesive layer / substrate 2 (5) Substrate 1 / anchor coat layer / barrier coat layer / printing layer / adhesive layer / substrate 2 However, the forms of the present disclosure are not limited to these.

[0090] Although the substrate 2 is not particularly limited, in some embodiments, a polyolefin resin having heat sealability can be suitably used. Examples of such a polyolefin resin include a corona-treated biaxially oriented polypropylene (OPP) film, a high-density polyethylene film (HDPE), a non-oriented polypropylene (CPP) film, a linear low-density polyethylene (LLDPE) film, and a PE resin film formed by melt coating. The thickness of the substrate 2 is not particularly limited, but from the viewpoint of processability during production of the packaging container, it is preferably 5 to 150 μm, and more preferably 10 to 70 μm.

[0091] In the laminate, by using a single material for the substrate 1 and the substrate 2, the recycling efficiency of the laminate can be increased. Since the aqueous barrier coating agent of the present disclosure contains polyvinyl alcohols and ethylene-vinyl alcohol copolymers, by using an olefin resin for the substrate 1 and the substrate 2, the recycling efficiency of the entire laminate can be increased.

[0092] Further embodiments of the present disclosure are given below, but the present disclosure is not limited to the following embodiments. The present disclosure relates to an aqueous barrier coating agent comprising a hydrophilic resin, an inorganic layered compound, and an aqueous medium, wherein the hydrophilic resin comprises polyvinyl alcohol and / or an ethylene-vinyl alcohol copolymer, and the aqueous barrier coating agent has a viscosity change rate represented by the following (Formula 1) of 30% or less. (Formula 1) Viscosity change rate = |Viscosity B - Viscosity A| / Viscosity A x 100 (In the above formula 1, viscosity A represents the viscosity at 25°C of the aqueous barrier coating agent immediately after production or stored at a temperature of 15 to 35°C after production, and viscosity B represents the viscosity of the aqueous barrier coating agent measured at 25°C after leaving the aqueous barrier coating agent at rest at 5°C for 24 hours.)

[0093] The present disclosure also relates to a method for producing an aqueous barrier coating agent containing a hydrophilic resin, an inorganic layered compound, and an aqueous medium, the method being characterized in that the hydrophilic resin contains polyvinyl alcohol and / or an ethylene-vinyl alcohol copolymer, the aqueous medium contains water and normal propanol, and the hydrophilic resin is dissolved in water at 90°C or higher for one hour or more (however, this does not include the barrier coating agent whose pot life when stored at room temperature is 24 hours or less). EXAMPLES

[0094] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the present invention, parts and % represent parts by mass and % by mass unless otherwise noted.

[0095] (Manufacturing of water-based barrier coating agents) <Example 1> 6 parts of ethylene-vinyl alcohol copolymer PVA1 (ethylene content: 8 mol%, solid content 100%) and 64 parts of water were heated with stirring, and continued to be heated and stirred at 95°C for 1 hour, after which heating was stopped and stirring was continued until the temperature returned to room temperature, 28 parts of normal propanol was added, and mixed and stirred to obtain an aqueous solution of ethylene-vinyl alcohol copolymer PVA1. 2 parts of montmorillonite (particle aspect ratio: 500, solid content 100%) was added to the aqueous solution of ethylene-vinyl alcohol copolymer PVA1, mixed, and dispersed with a disperser for 20 minutes to obtain an aqueous barrier coating agent V1.

[0096] <Examples 2 to 16 and Comparative Examples 1 to 6> Aqueous barrier coating agents V2 to 22 were obtained in the same manner as in Example 1, except that the raw materials, compounding ratios, and dispersion methods shown in Table 1 were used. In Example 15, the degree of dispersion treatment was weakened compared to Example 1 so that the average particle size (D50) became coarser. The properties of the raw materials used are as follows:

[0097] Polyvinyl alcohol PVA5: Saponification degree 98% or more, solid content 100% Ethylene-vinyl alcohol copolymer PVA2: ethylene content 2 mol%, solid content 100% Ethylene-vinyl alcohol copolymer PVA3: ethylene content 14 mol%, solids content 100% Ethylene-vinyl alcohol copolymer PVA4: ethylene content 27 mol%, solids content 100% Water-soluble acrylic resin A1: AQUALIC HL415, manufactured by Nippon Shokubai Co., Ltd., weight average molecular weight 10,000, solid content 45%

[0098] Montmorillonite: Kunimine Kogyo Co., Ltd., Kunipia F, layered compound, aspect ratio 500, solid content 100% Hectorite: BYK, LAPONITE-S482, layered compound, aspect ratio 25, 100% solids Kaolinite: Hayashi Kasei Co., Ltd., Hydrite SB100, layered compound, aspect ratio 100, solid content 100% Natural mica: Yamaguchi Mica Co., Ltd., TM-10, layered compound, aspect ratio 130, solid content 100% Silica particles: Mizusawa Chemical Industry Co., Ltd., Mizukasil P-707, non-layered compound, average particle size (laser scattering method): 4 μm, oil absorption: 250 ml / 100 g, solid content 100% Sodium salt compound: Sodium tripolyphosphate, manufactured by Taihei Chemical Industry Co., Ltd., solid content 100%

[0099] <Measurement of viscosity change rate> The obtained coating agents V1 to 22 were placed in a sealed container and left to stand for 24 hours at 5° C. After that, the viscosity of the coating agents V1 to 22 after the standing was measured at a temperature of 25° C., and the viscosity change rate was calculated by the following formula 1. The viscosity of the coating agent is a value measured using a Zahn cup. Specifically, a stainless steel cup (Zahn cup No. 3 manufactured by Rigo Co., Ltd.) with an orifice diameter of 3 mm and a capacity of 43 ml is used, and the cup is immersed in the sample at a temperature of 25°C and quickly pulled up with a constant movement. The number of seconds from the moment the bottom of the cup leaves the liquid surface to the moment the flow of the sample (steady flow) flowing out of the orifice stops is used as viscosity A and viscosity B in the following formula.

[0100] For example, in the case of V1 in Example 1, the viscosity measured at a temperature of 25°C (viscosity A) was 18 seconds, and after standing at 5°C for 24 hours, the viscosity measured at a temperature of 25°C (viscosity B) was 18 seconds. Therefore, according to the following formula 1, the viscosity change rate is 0%. (Formula 1) Viscosity change rate = |Viscosity B - Viscosity A| / Viscosity A x 100 Viscosity change rate in Example 1 = |18-18| / 18×100 = 0

[0101] (Printing of water-based barrier coatings) <Example 1> Coated material p1, laminate P1 The aqueous barrier coating agent V1 was printed twice on the entire surface of the corona-treated machine-length-direction-oriented polyethylene (MDOPE) film (thickness 20 μm) using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm under the conditions of a printing speed of 40 m / min and an in-line oven temperature of 70°C to form a barrier coat layer, and a coating material p1 of MDOPE (substrate 1) / barrier coat layer was obtained. Next, a polyether-based reactive urethane adhesive ("TM-340V / CAT-29B" manufactured by Toyo Morton Co., Ltd.) was applied onto the barrier coat layer of the coating material p1 using a dry laminator, the solvent was dried in an oven to form an adhesive layer, and then a linear low-density polyethylene (LLDPE) film (thickness 30 μm) was laminated onto the adhesive layer at a line speed of 40 m / min and kept at 40°C for one day to obtain a laminate P1 having a configuration of MDOPE (substrate 1) / barrier coat layer / adhesive layer / LLDPE (substrate 2). The coating weight of the barrier coat layer of the laminate P1 after drying was calculated using the following method and was 1.0 g / m 2 It was.

[0102] <Examples 2 to 16, Comparative Examples 1 to 6> Coated materials p2 to 22, laminates P2 to 22 Printing was carried out on V2 to V22 in the same manner as in Example 1 to obtain coated objects p2 to p22 and laminates P2 to P22.

[0103] (Printing after aging with water-based barrier coating) <Examples 1 to 16, Comparative Examples 1 to 6> Coated materials Q1 to 22, laminates Q1 to 22 Coating agents V1 to 22 were placed in standard glass bottles, and the bottles were allowed to stand at 5° C. for one week in a sealed state with a lid on. Printing was then carried out in the manner described above to obtain coated objects q1 to 22 and laminates Q1 to 22.

[0104] <Method of measuring coating amount> Five 10 cm square samples of the film substrate / barrier coat layer were cut out from the film substrate / barrier coat layer component in the coating obtained by the above method, and five 10 cm square samples of the film substrate were cut out from the film substrate. The mass of each sample was measured, and the coating weight of the barrier coat layer was calculated using the following formula 8. The film substrate was a corona-treated machine-length-oriented stretched polyethylene (MDOPE) film (thickness 20 μm). (Equation 8) Coating weight of barrier coat layer (g / m 2 ) = (average weight of five samples of film substrate / barrier coat layer) - (average weight of five samples of film substrate)

[0105] <Dispersion stability> The obtained aqueous barrier coating agents V1 to 22 were placed in standard glass bottles, and left to stand at 5°C for one week in a sealed state with a lid on. The condition of the aqueous barrier coating agents was then visually observed and evaluated according to the following criteria, where A, B, and C are ranges that are acceptable for practical use. A: No precipitation, no gelation B: Precipitation, no gelation, usable with stirring C: No precipitation, gelation, usable with stirring D: No precipitation, gelation, not usable

[0106] <Oxygen barrier properties> The obtained laminates P1 to 22 and Q1 to 22 were cut into pieces measuring 100 mm x 100 mm, and the oxygen permeability (cc / m) was measured in an atmosphere of 23°C and 65% RH using a MOCON OX-TRAN2 / 22. 2 The thermal conductivity (Tc) of the resin was measured and evaluated according to the following criteria, with A, B, and C being acceptable for practical use. <<Evaluation Criteria>> A: Oxygen permeability is 1cc / m 2 ·day·atm. B: Oxygen permeability is 1cc / m 2 ·day ·atm or more, 5cc / m 2 ·day·atm. C: Oxygen permeability is 5cc / m 2·day ·atm or more, 20cc / m 2 ·day·atm. D: Oxygen permeability is 20cc / m 2 ·day ·atm or more, 100cc / m 2 ·day·atm. E: Oxygen permeability is 100cc / m 2 ·day·atm or higher.

[0107] [Table 1-1]

[0108] [Table 1-2]

[0109] [Table 2]

[0110] From the above results and the results of each Example, it can be seen that the barrier coating agent containing normal propanol together with a hydrophilic resin and an inorganic layered compound was stored at low temperature, and then the laminate Q produced using this had good oxygen barrier properties. Comparative Example 1 did not contain polyvinyl alcohol or ethylene vinyl alcohol, and therefore had poor oxygen barrier properties. Comparative Examples 2 and 3 did not contain an inorganic layered compound, and therefore had poor oxygen barrier properties. Comparative Examples 4 and 5 did not contain normal propanol, and gelation occurred in the barrier coating agent after low-temperature storage.

Claims

1. The composition includes a hydrophilic resin, an inorganic layered compound, and an aqueous medium, the hydrophilic resin comprises at least one selected from the group consisting of polyvinyl alcohol, an ethylene-vinyl alcohol copolymer having an ethylene content of 25 mol% or less, and modified products thereof; 1. An aqueous barrier coating agent, wherein the aqueous medium comprises normal propanol and water, the content of water in the total mass of the aqueous medium being 50 mass% or more, and the content of isopropanol in the total mass of the aqueous medium being 15 mass% or less.

2. 2. The aqueous barrier coating agent according to claim 1, wherein the ethylene-vinyl alcohol copolymer has an ethylene content of 20 mol % or less.

3. 3. The aqueous barrier coating agent according to claim 1, wherein a viscosity change rate represented by the following formula 1 is 30% or less. (Formula 1) Viscosity change rate = | Viscosity B - Viscosity A | / Viscosity A x 100 (In the above formula 1, viscosity A represents the viscosity at 25°C of the aqueous barrier coating agent immediately after production or stored at a temperature of 15 to 35°C after production, and viscosity B represents the viscosity of the aqueous barrier coating agent measured at 25°C after standing at 5°C for 24 hours. Viscosity A and viscosity B are each the number of seconds (seconds) until flow in viscosity measurement using a Zahn cup No. 3.)

4. 3. The aqueous barrier coating agent according to claim 1, wherein the hydrophilic resin accounts for 50 to 95% by mass of the total solid content of the aqueous barrier coating agent.

5. 3. The aqueous barrier coating agent according to claim 1, wherein the n-propanol accounts for 5 mass % or more of the total mass of the aqueous medium.

6. 3. The aqueous barrier coating agent according to claim 1, wherein the total content of the secondary monoalcohol and the tertiary monoalcohol is 15 mass % or less based on the total mass of the aqueous medium.

7. 3. The aqueous barrier coating agent according to claim 1, wherein the inorganic layered compound comprises at least one selected from the group consisting of montmorillonite, kaolinite, and natural mica.

8. 3. The aqueous barrier coating agent according to claim 1, wherein the inorganic layered compound comprises an inorganic layered compound having an aspect ratio of 50 to 1000.

9. 3. The aqueous barrier coating agent according to claim 1, wherein the inorganic layered compound comprises sodium ions.

10. 3. The aqueous barrier coating agent according to claim 1, further comprising a sodium salt compound.

11. 3. The aqueous barrier coating agent according to claim 1, wherein the inorganic layered compound in the aqueous barrier coating agent has an average particle size (D50) of 3 μm or less according to a laser diffraction / scattering method.

12. 3. The aqueous barrier coating agent according to claim 1, wherein the inorganic layered compound accounts for more than 20% by mass and not more than 40% by mass of the total solid content of the aqueous barrier coating agent.

13. 3. The aqueous barrier coating agent according to claim 1, wherein the inorganic layered compound contains montmorillonite, and the content of the montmorillonite in the inorganic layered compound is 50 to 100% by mass.

14. A printed matter comprising a substrate and a barrier coat layer formed from the aqueous barrier coating agent according to claim 1 or 2.

15. 3. A laminate comprising: a substrate 1; a barrier coat layer formed by the aqueous barrier coating agent according to claim 1; and a substrate 2, with the barrier coat layer being interposed between the substrate 1 and the substrate 2.

16. A hydrophilic resin containing at least one selected from the group consisting of polyvinyl alcohol, an ethylene-vinyl alcohol copolymer having an ethylene content of 25 mol% or less, and modified products thereof, and water are mixed, and the temperature is controlled at 80°C or more for 1 hour or more to provide a pre-hydrophilic resin composition; Mixing the pre-hydrophilic resin composition and normal propanol to obtain a hydrophilic resin composition; and mixing the hydrophilic resin composition and an inorganic layered compound to provide an aqueous barrier coating agent; The aqueous barrier coating agent is produced by the method of the present invention, wherein the aqueous medium contains normal propanol and water, the content of water in the total mass of the aqueous medium is 50 mass% or more, and the content of isopropanol in the total mass of the aqueous medium is 15 mass% or less.

Citation Information

Patent Citations

  • Dispersion composition and film

    JP2003231789A

  • Resin composition and its applications

    JP2003268183A

  • Coating composition

    JP2006282947A

  • Gas barrier laminated film

    JP2011031455A

  • Gas barrier laminate and its manufacturing method

    JP2005144761A